Letter : Medical aid for Spain - Witt, L.
042-0087-001 THE JOINT COUNCIL of the SOUTHAMPTON TRADES COUNCIL, LABOUR PARTY and CO-OPERATIVE SOCIETY PROSPECT HOUSE, 160 ABOVE BAR, SOUTHAMPTON Hon. Secretary : Mr. L. WITT Telephone : 5191 Southampton Trades Council Hon. Secretary : Mr. R. Chick 107 Earls Road Southampton Labour Party Secretary and Agent : Mr. A. Rose 54 Henstead Road Telephone : 2427 Southampton Co-operative Society, Ltd. (Development Committee) Secretary : Mr. L. Witt, Prospect House 160 Above Bar Telephone : 5191 PLEASE ADDRESS YOUR REPLY T0:- "Upwey" , Hatley Road, Bitterne, Southampton. Sir Walter Citrine, General Secretary, National Council of Labour, Transport House, Smith Square, London, S.W.1. Dear Sir, MEDICAL AID FOR SPAIN. Your Ref: - WMC/EAB/15. INTERNATIONAL. Enclosed please find cheque value £7. 14. 5. being the balance of the total amount raised by this Council for MEDICAL AID FOR SPAIN. This makes a total sent to you of £307: 14: 5. RAY COX MEMORIAL. I beg to refer to your letter, undated, which was a further letter to yours of 5th October, 1937, regarding a photograph of the apparatus purchased for the Ray Cox Memorial. Have you yet been able to obtain a copy of this photograph ? Yours sincerely, L. Witt Hon. Sec. 292/946/42/87